Empirical study of work-life balance and organizational commitment in tin can island port terminals, Lagos State, Nigeria - Okolie, Ugo Chuks; Mukoro, Akpo Muvire; Otite, Atare (Universitas Negeri Yogyakarta, 2024)
Despite the benefits of work-life balance and the large number for studies it has motivated in developed nations, relatively little studies have been done on how it affects organisational commitment in Nigeria. This is because Nigerian businesses are known for endorsing unstable working environments and unethical workplace standards at the expense of the wider public. In light of this, this study examined the connections between organisational commitment and work-life balance in the Tin Can Island Port terminals in Lagos State. Purposive sampling was used in conjunction with the cross-sectional approach. The work enrichment theory served as the study's theoretical framework, and a questionnaire with 389 respondents was used as the research instrument. Statistical Package for Social Sciences (SPSS) Version 23 was used to analyse the data using percentages, mean, standard deviation, Pearson's coefficient of correlation, and both linear and multiple regression analysis. The study's conclusions demonstrated how employees' affective, continuance, and normative commitments were impacted by work-life balance in Tin Can Island Port, Lagos State. The study came to the conclusion that employees' commitment to their organisation as well as their personal lives, are impacted by an inadequate work-life balance. Based on the study's findings and conclusion, the management of Tin Can Island Port should, among other things, develop and successfully apply flexible work schedules to help staff members manage and lessen the conflicts they encounter in their personal lives.